Treatment And Prevention Of Periodontitis In The Early Stages Of The Disease (Texas Journal of Medical Science, 2024)
An analysis of the results of a dental examination in Andijan region (2017–2019) showed a high prevalence of signs of periodontal tissue damage. In these conditions, emphasis is needed on the active introduction of prevention at the individual level and the establishment of new forms of organization of specialized periodontic care.